Omicron: A Grim Reality Amidst COVID-19 - Mazhar, Saima; Tanwir, Farzeen; Mehwish, Ayesha; Mahar, Yasmeen; Baqar, Anum; Quereshi, Maryam Faiz; Younis, Areeba; Naveed, Ariba; Haseeb, Syed Wajahat; Khan, Mahail; Khattak, Mariya Azam (Novel Aspects on Pharmaceutical Research Vol. 2, 2023)
Since the outbreak of the plague Covid-19, which has killed more than 5.57 million people worldwide, the world has been in pain for the past two and a half years. The spread of new coronavirus Omicron variants after alpha, beta, gamma, and delta continues. The virus, which was discovered in Botswana and South Africa in November, has spread rapidly throughout the world in recent weeks, outpacing any previously known coronavirus variant. When compared to other variants, Omicron has been shown to be highly contagious and less receptive to vaccines. November 26, 2021, was when the omicron variant was classified as a variant of concern by the WHO (CDC, 2021) [1]. The goal of this study was to provide a brief overview of what we already know about the Omicron virus and what more needs to be learned about its various variants.